Analisis Faktor-Faktor Yang Mempengaruhi Potensi Penerimaan Opini Audit Going Concern Pada Perusahaan Manufaktur - Rani Meisya Fitriyani; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Going concern opinion is an important aspect in assessing the operational sustainability of a company. The purpose of this article is to analyze the factors that influence the possibility of obtaining a going concern opinion in manufacturing companies. This research uses a quantitative approach by collecting primary data from a number of manufacturing companies through surveys and secondary data from financial reports. The independent variables considered include financial ratios, operating results, company size, and the quality of corporate governance. Logistic regression analysis is used to test the relationship between the independent and dependent variables, namely the possibility of receiving a going concern opinion. Our analysis shows that financial indicators such as the current ratio, debt to equity ratio, and profitability have a significant effect on the ability to obtain a going concern opinion. Apart from that, business performance and the quality of company management also play an important role in determining business continuity opinions. These results provide valuable insight for management, auditors and regulators to understand the factors that may influence the assessment of going concern opinion of a manufacturing company.